2007
DOI: 10.1074/jbc.m704213200
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Diacylglycerol Acyltransferase-2 (DGAT2), but Not DGAT1, with Antisense Oligonucleotides Reverses Diet-induced Hepatic Steatosis and Insulin Resistance

Abstract: Nonalcoholic fatty liver disease (NAFLD) is a major contributing factor to hepatic insulin resistance in type 2 diabetes. Diacylglycerol acyltransferase (Dgat), of which there are two isoforms (Dgat1 and Dgat2), catalyzes the final step in triglyceride synthesis. We evaluated the metabolic impact of pharmacological reduction of DGAT1 and -2 expression in liver and fat using antisense oligonucleotides (ASOs) in rats with diet-induced NAFLD. Dgat1 and Dgat2 ASO treatment selectively reduced DGAT1 and DGAT2 mRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
291
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 342 publications
(314 citation statements)
references
References 55 publications
19
291
4
Order By: Relevance
“…1F). ASOs have been previously shown not to distribute to muscle and not to cause reduction in gene expression in this tissue (6,17,18). Additionally, we tested the transcription of SirT1 in the hypothalamus as a possible explanation for the decreased food intake and found no differences in mRNA (control ASO 1.00 Ϯ 0.14 vs. SirT1 ASO 1.08 Ϯ 0.13) on the normal chow diet.…”
Section: Resultsmentioning
confidence: 99%
“…1F). ASOs have been previously shown not to distribute to muscle and not to cause reduction in gene expression in this tissue (6,17,18). Additionally, we tested the transcription of SirT1 in the hypothalamus as a possible explanation for the decreased food intake and found no differences in mRNA (control ASO 1.00 Ϯ 0.14 vs. SirT1 ASO 1.08 Ϯ 0.13) on the normal chow diet.…”
Section: Resultsmentioning
confidence: 99%
“…While TGs are now considered to be a metabolically inert storage pool [11,17], it remains unclear which bioactive lipid species may be most important in the induction of insulin resistance. Many studies have reported increased levels of DGs or ceramides in insulin-resistant states and have demonstrated that reductions in these lipid species can improve insulin action [5,[9][10][11][12][14][15][16]. One mechanism through which these lipid species have been proposed to drive insulin resistance is through antagonism of the insulin-signalling cascade [4,12].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated DGs in muscle and liver are associated with insulin resistance in humans [5,6] and animals [7,8]. Genetic manipulations in rodents that alter DG levels also support a role for this lipid intermediate as an important mediator of insulin action [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…DGAT1 and DGAT2 account for nearly all TG synthesis in mammalian cells (29), and both enzymes reside in the ER, although they are found in distinct ER microdomains (30). Both DGATs have been implicated in the development of diet-induced hepatic steatosis (31)(32)(33). However, although DGAT2 deficiency in mice is lethal early after birth, DGAT1 deficiency protects against hepatic steatosis in both diet-induced obesity and fasting paradigms, but it has no effect on steatosis in situations where de novo lipogenesis is increased (32).…”
mentioning
confidence: 99%